KIAT–KIAT MERINTIS USAHA DALAM PENGEMBANGAN EKONOMI KREATIF MENUJU DESA WISATA PADA PEMUDA DI MA ISHLAIL ATHFAL RUMAK KECAMATAN KEDIRI - Netrawati , I Gusti Ayu Oka; Suharti, Suharti; Permadi, I Gusti Agung Didit Eka; Ibroni, Ibroni; Efendi, Hayati; Heriyana, Nonik (LPPM Institut Pendidikan Nusantara Global, 2023)
People are becoming familiar with home industries that sell creative ideas to generate income. Entrepreneurship is essentially the nature, characteristics, and character of a person who has the will to creatively realize innovative ideas in the real world. Villages have the potential that can be developed into tourist villages, namely natural potential, human resource potential, and cultural potential. In this millennial era, young people are required to think creatively and innovatively. Creative economic development towards a tourist village for youth at MA Ishlahil Athfal Rumak, Kediri District, West Lombok Regency which begins with starting a business as an entrepreneur will encourage the acceleration of community economic growth in Rumak Village, Kediri District, West Lombok Regency. The conclusion obtained from this community service activity is that the creative economic development of youth at MA Ishlahil Athfal Rumak, Kediri District in building a tourist village after the implementation of community service activities is the formation of a change in the mindset of young people to pioneer a business which will later provide tourism village development for Rumak Village in Kediri District. Suggestions that can be given for the development of a creative economy for a tourist village are to build types of businesses such as souvenirs, handicrafts, and art.